2003
DOI: 10.1242/jcs.00695
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis uses host cell dynein to traffic to the microtubule-organizing center in a p50 dynamitin-independent process

Abstract: Chlamydiae are pathogenic obligate intracellular bacteria with a biphasic developmental cycle that involves cell types adapted for extracellular survival (elementary bodies, EBs) and intracellular multiplication (reticulate bodies, RBs). The intracellular development of chlamydiae occurs entirely within a membrane-bound vacuole termed an inclusion. Within 2 hours after entry into host cells, Chlamydia trachomatis EBs are trafficked to the perinuclear region of the host cell and remain in close proximity to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
184
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(192 citation statements)
references
References 47 publications
6
184
1
1
Order By: Relevance
“…Microtubules are also required for the intracellular movement and cell-to-cell spread of Actinobacillus actinomycetemcomitans (Meyer et al, 1999), and both microtubules and dynein have previously been found to localise around Chlamydia Journal of Cell Science 117 (7) trachomatis-containing vacuoles several hours after infection of epithelial cells (Clausen et al, 1997). Dynein activity is required for migration of C. trachomatis to the peri-Golgi region, although this appears to be independent of p50/dynamitin (Grieshaber et al, 2003). The recent finding from our laboratory that Salmonella microcolonies also develop in close association with the Golgi (Salcedo and Holden, 2003) provides further evidence of similarities in the behaviour of these two intracellular pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules are also required for the intracellular movement and cell-to-cell spread of Actinobacillus actinomycetemcomitans (Meyer et al, 1999), and both microtubules and dynein have previously been found to localise around Chlamydia Journal of Cell Science 117 (7) trachomatis-containing vacuoles several hours after infection of epithelial cells (Clausen et al, 1997). Dynein activity is required for migration of C. trachomatis to the peri-Golgi region, although this appears to be independent of p50/dynamitin (Grieshaber et al, 2003). The recent finding from our laboratory that Salmonella microcolonies also develop in close association with the Golgi (Salcedo and Holden, 2003) provides further evidence of similarities in the behaviour of these two intracellular pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Soon after entry, nascent inclusions are transported along microtubules to the microtubule organizing center (MTOC) in a dynein-dependent but dynactin-independent manner (Clausen et al 1997;Grieshaber et al 2003;Grieshaber et al 2006), suggesting that one or more unknown bacterial effectors mimic the cargobinding activity of dynactin and tether the inclusion to dynein and/or to centrosomes. Src family kinases are required in human-adapted Chlamydia strains for inclusions to migrate to the MTOC and for intracellular growth, even though they are dispensable for binding and entry (Mital and Hackstadt 2011).…”
Section: Transport To the Peri-golgi Regionmentioning
confidence: 99%
“…As obligate intracellular parasites the microsporidia appear to have been able to reduce their genome size, simplify their organelle structures and reduce their biochemical pathways by subverting the host cell's physiology to provide the missing biochemical support for parasite development (Slamovits et al 2004). As with other intracellular parasites, from viruses to protozoa (e.g., Halonen and Weidner 1994, Risco et al 2002, Grieshaber et al 2003, the microsporidia appear to modify host cell cytoskeleton, organelle arrangement, biochemistry and cell cycle to optimize the intracellular niche (Weidner et al 1999, Scanlon et al 2000. To date, compared with many other infectious agents, relatively little is known about how the microsporidia signal the host cells to affect these many changes that occur in host cell structure and function.…”
Section: Multinucleate Host Cells Induced By Vittaforma Corneae (Micrmentioning
confidence: 99%